WHITNEY CHAPPELL (ED.) (2019): Recent Advances in the Study of Spanish Sociophonetic Perception, Amsterdam/Philadelphia, John Benjamins. - Chelsea Escalante (Estudios de Fonética Experimental, 2019)
[to be added]